Job Guarantee program and the kaleckian dilemma: Lessons from the Rehn-Meidner plan - Caio Vilella; Eduardo F. Bastian (Levy Economics Institute of Bard College, 2024)
Minsky (1965) has presented the Job Guarantee program as a recommendation in the war against unemployment and poverty. Kalecki (1943), on the other hand, argued that the full employment situation could be technically feasible but politically hard to implement due to the class struggle, resulting in what we will refer to as the "kaleckian dilemma". Based on this contradiction, this paper aims to extract lessons from the Rehn-Meidner Swedish plan, which successfully combined low unemployment rates and creeping inflation for over three decades, as a means to study the chances of a Job Guarantee overcoming the kaleckian dilemma. From these lessons, this piece highlights the importance of a tripartite council bargaining board at the national level to settle the Job Guarantee's wage level. In addition, we highly recommended other desirable features, such as international capital control and taxation on extraordinary profits, to raise the chances of the program successfully dealing with the kaleckian dilemma, just as Rehn-Meidner did.
Keywords: E11; E31; H53; I30; 330; Kaleckian dilemma; Job Guarantee; Rehn-Meidner plan